Molecular Identification of Endophytic Fungi from Bark of Raru (Cotylelobium melanoxylon) that Produce the Antibacterial Compounds - Uswatun Hasanah; Riwayati Riwayati; Idramsa Idramsa; Eko Prasetya (Biosaintifika: Journal of Biology & Biology Education, 2017)
The Dipterocarpaceae plant, raru (Cotylelobium melanoxylon) is widespread in Southeast Asia. The bark of raru has been used by local communities in North Sumatera as antidiarrheal drugs due to its antibacterial compounds. The antibacterial activity of the raru’s bark is induced by endophytic fungi that live in the region of the bark. This study aimed to identify the endophytic fungi-producer of antibacterial compounds in the bark of raru (C. melanoxylon) by means of molecular analysis. In general, endophytic fungi have the ability to inhibit the growth of pathogenic bacteria. Thirty-eight isolates of endophytic fungi were isolated from the bark of raru. Selection of isolates for antibacterial activity against Escherichia coli ATCC 35218 and Staphylococcus aureus ATCC 25923 used the dual culture assay. Selection using the dual culture assay yielded 6 endophytic fungal isolates that have the ability to inhibit the growth of test bacteria. EF10A sample was the most powerful isolate inhibiting the growth of both bacteria test. Those six bacteria molecularly identified used a sequence generated from ITS rDNA region. Based on rDNA ITS region sequences, isolate, the producers of the antibacterial compound were identified as Talaromyces cellulolyticus, Penicillium purpurogenum, Aspergillus sp., Trichoderma harzianum, and Aspergillus orizae. The results of this study can be used by researchers to explore more potential endophytic fungi in raru plants (C. melanoxylon) as a source of medicine. The data obtained need to be supported by further research to isolate the bioactive compounds that can inhibit the growth of microbial pathogens.